Tail and fin rot bacteria in Icelandic aquaculture. Diversity and genetic analysis - Guðbjörg Guttormsdóttir 1989- (2017)
Tail and fin rot, caused by Flavobacterium and Tenacibaculum bacteria, is an emerging disease worldwide that has recently been detected in Icelandic aquaculture. Infected fish can display open lesions, tissue damage and tail and fin rot. The symptoms can vary in severity from metachromatic skin to systemic infection. In this study, pathogenic bacteria of fish in the genera Flavobacterium and Tenacibaculum were studied; Flavobacterium psychrophilum, Flavobacterium columnare, Flavobacterium branchiophilum, Tenacibaculum maritimum and Tenacibaculum soleae. The cells are Gram-negative, slender rods that appear pale yellow or yellow on agar plates. Identification of the etiological agent can be difficult when based solely on bacterial culture, as the Flavobacterium and Tenacibaculum species are slow growing bacteria that are easily overgrown by contaminating bacteria. To improve the power of identification, polymerase chain reaction (PCR) and DNA sequencing were applied. The objective of this study was to isolate the etiological agents of tail and fin rot from diseased Icelandic fish, both farmed and wild caught, and analyze them using molecular analysis. Yellow pigmented colonies that resembled tail and fin rot bacteria were examined under a light microscope and Gram-stained, after which the 16S rRNA gene was amplified and sequenced to confirm the bacterial identity. The 16S rRNA gene sequences of the Icelandic isolates were furthercompared to those of published isolates by phylogenetic analysis. The Neighbor-Joining phylogenetic tree displayed great variance within many of the Flavobacterium isolates in Iceland and many isolates prove to be unrelated to the F. psychrophilum reference strain. Some isolates, however, group together with the reference strain. Numerous primers have been published that are supposedly species-specific. However, upon further examination, species-non-specific amplification appears to be common. Although the Flavobacterium and Tenacibaculum species are related, comparison of the 16S rRNA ...